Transfererscheinungen zu Beginn des L3-Erwerbs: Evidenz aus der schriftlichen Sprachproduktion mehrsprachiger Deutschlerner - Długosz, Kamil (Państwowa Akademia Nauk, 2018)
This paper investigates the phenomenon of language transfer at the initial state of third language acquisition by adult Polish learners of English (L2) and German (L3). First, the controversy between two conflicting theories of language acquisition, behaviorism and nativism, is discussed with regard to cross‑linguistic interactions. Second, some influential models of third language acquisition are presented. The participants' written production data from 122 essays was analyzed and interpreted in terms of language transfer. Evidence for both L1 and L2 transfer could be found. The results show, however, that the influence of L2 is more robust and primarily affects the lexicon. Finally, the present paper emphasizes the fact that language transfer should not be perceived as a source of errors, but rather as an inevitable result of the third language acquisition process.
Keywords: transfer międzyjęzykowy; akiwzycja języka trzeciego; wpływy międzyjęzykowe; interjęzyk; natywizm; interjęzyk; cross-linguistic influence; language transfer; interlanguage; third language acquisition